Attacks and Spatial Distribution of Clove Stem Borer in Southeast Minahasa Regency - Elisabet R.M. Meray; Rante, Caroulus Simbalis; Betsy Pinaria (Universitas Sam Ratulangi, 2025)
The main problem encountered in the field is the attack of borer pests that attack the stems of clove plants. This study aims to determine the types, percentage of attacks, and spatial distribution patterns of stem borers attacking clove plants in Southeast Minahasa Regency. The research method was to directly observe the symptoms of attacks by clove stem borers that had been randomly identified in several villages. The spatial distribution pattern was analyzed using the Standardized Morosita Index (Ip). The results of the study showed that the type of stem borer pest attacking clove plants in Southeast Minahasa Regency was Hexamitodera semivelutina Hell. (Coleoptera: Cerambycidae). The average percentage of stem borer pest attacks, H. semivelutina, in Pasan Subdistrict was highest in Liwutung 1 Village (33.50%) and lowest in Towuntu Village (25.10%); in East Ratahan District, the highest average percentage of attacks was in Wioi Village (30.40%) and the lowest in Wioi 3 Village (26.30%); while in Belang District, the highest average percentage of attacks was in Watuliney Village (29.90%) and the lowest in Belang Village (19.60%). Overall, the average percentage of attacks by the stem borer, H. semivelutina, in Southeast Minahasa Regency was 27.92%, ranging from 19.60% to 33.50%. The distribution pattern of the stem borer pest, H. semivelutina, in Southeast Minahasa Regency spreads in clusters with an Ip value of 2.16.